Cultural intelligence in intercultural collaborative music-making: Self-reflecting on interpersonal abilities as a mediator for creative collaborations in Colombia - Saarenkylä, Viivi Maria (Taideyliopiston Sibelius-Akatemia, 2023)
In this artistic research, I investigate the personal and interpersonal abilities of a musician in intercultural musical collaborations. The body of this research is my field trip to Colombia and two different artistic collaboration projects that I carried out during this trip. I apply the theoretical concept of cultural intelligence to observe and understand my personal experience in engaging in intercultural collaborative music-making. As an artist-researcher, I look into the distinctive characteristics of interpersonal interaction with culturally different others and I answer the following research questions: 1. How does cultural intelligence emerge in intercultural creative collaboration? 2. How can cultural intelligence and intercultural communicative competence impact the creative outcome in intercultural and transcultural collaborations? As the research method, I use artistic autoethnography. I focus on self-reflecting on my personal experience in Colombia and describe insights relating to the key concepts which are cultural intelligence, intercultural communicative competence, and intercultural collaboration. Through the observations, I aim to contribute new knowledge on these key concepts as applied in artistic research and creative artistic practices. As emerging in the findings, cultural intelligence and developing personal abilities in intercultural understanding and adaptation form a foundation for successful interpersonal encounters and collaborations in culturally diverse environments. Simultaneously, creative artistic collaborations can help in absorbing cultural understanding and succeeding in intercultural communication. Along with a thesis, this artistic research includes two artistic components: a music video as an outcome of a song-writing collaboration and an extended play release (EP) of three improvised musical pieces.
Keywords: intercultural; artistic research; autoethnography; communication; intercultural interaction; collaboration; cultural intelligence; communicative competence; intercultural competence; transcultural; collaborative music-making; kulttuurienvälisyys; kulttuurienvälinen viestintä; musiikki; taiteellinen tutkimus; vuorovaikutus; monikulttuurisuus; luovuus; kulttuuriosaaminen; Glomas